Improving the Integrity of Public Procurement Systems through Control and Information Management Systems. Perspective from the Internal Management of a Purchasing Cycle - Ochsenius Robinson, Iván (Revista del CLAD Reforma y Democracia, 2023)
While progress has been made in public procurement or contracting -in general- in regulatory issues and in a complementary article to the law itself, it has not been enough to improve procurement systems both in terms of the way they operate, as well as in reducing bad practices or acts of corruption. Traditional control systems are not enough, nor is the application of the same work dynamics and the management of the information generated by the process. It is here that integrity and an operational framework could play an important role, especially if it is developed from the point of view of control, information management systems and a managerial vision that encompasses and directs the above. In order for public procurement to play a strategic role and comply with environmental, social and innovative criteria so demanded by these times and, above all, to provide the benefit of timely, effective, efficient and transparent acquisition, it is imperative: to insert it within a framework of integrity that guarantees the use of resources in a transparent and accountable manner; a respect for the law and ethical frameworks; an optimal internal management of all available means. It is therefore essential to manage this integrity from a vision that encompasses the entire procurement cycle, where the analysis and ongoing management of its stages show not only that the regulations and ethics are being complied with, but above all, what elements are not adding value. The aim of this document is to point out the importance of control, information management systems, and a managerial and holistic vision in a public procurement cycle, seeking to highlight operational aspects in them that can improve and/or reinforce each stage of this process and its results in relation to the concept of integrity. Likewise, this work wishes to complement the mostly legalistic vision that is held of the operation of this procurement matter, as expresses by the World Bank (2016: 2): “in summary, public contracting is a business process within a public system”.